2011
DOI: 10.1002/jmor.10965
|View full text |Cite
|
Sign up to set email alerts
|

A new interpretation of stomatogenesis in a peritrich ciliate: Using Campanella umbellaria as a model system

Abstract: The process of stomatogenesis in peritrich ciliates is still incompletely understood. Previous studies on the stomatogenesis of four species of peritrichs, Telotrochidium sp., Carchesium polypinum, Opercularia coarctata, and Astylozoon pyriforme conflict with one another in some cases and omit details of events in others. We described the entire process of stomatogenesis in the peritrich ciliate Campanella umbellaria (C. umbellaria) using an improved method of staining with protargol. Our results disagree with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 34 publications
(114 reference statements)
2
26
0
Order By: Relevance
“…The articles by Wang et al. () and Wu et al. (), focusing on the large, colonial species Campanella umbellaria (Linnaeus, 1758) and Epistylis chlorelligerum Shen, 1980, were done with an improved method of silver staining with protargol and described differences in the details of stomatogenesis in these two species, supporting the hypothesis that most differences reported by previous investigators are probably genuine rather than the result of observational error.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…The articles by Wang et al. () and Wu et al. (), focusing on the large, colonial species Campanella umbellaria (Linnaeus, 1758) and Epistylis chlorelligerum Shen, 1980, were done with an improved method of silver staining with protargol and described differences in the details of stomatogenesis in these two species, supporting the hypothesis that most differences reported by previous investigators are probably genuine rather than the result of observational error.…”
mentioning
confidence: 77%
“…Studies on the stomatogenesis of peritrichs have confirmed that this appears to be true in a general sense, but at the same time, they have uncovered morphogenetic differences among the taxa investigated (Wang et al. ). In particular, there are differing descriptions of how the germinal anlage, the infundibular polykineties of the new oral complex, the new haplokineties, and the new germinal kineties of daughter cells are formed (Eperon ; Esteban and Fernández‐Galiano ; Fernández‐Galiano et al.…”
mentioning
confidence: 91%
See 3 more Smart Citations